Thermal Stability and Thermodynamic Performances of Pure Siloxanes and Their Mixtures in Organic Rankine Cycles - Di Marcoberardino, Gioele; Invernizzi, Costante Mario; Iora, Paolo; Arosio, Luca; Canavese, Marcello; Lunghi, Angelo; Mazzei, Antonella (Energies (Basel), 2022)
Organic Rankine cycles are often the best solution for the conversion of thermal energy. The many working fluids include silicon oils. One crucial issue that determines the choice of a working fluid is its thermochemical stability, as this sets a limit to the maximum temperature at which the fluid can be used in a power plant. A second subject, much debated today, is the use of mixtures in ORCs. In the first part of this study, an investigation into the thermal stability of siloxanes using two different approaches was carried out. The results confirmed a limit working temperature for the considered siloxanes of about 300 °C, with a degradation that advanced significantly over time at 350 °C. In the second part of the study, an analysis of the thermodynamic performances of some siloxane mixtures was carried out. It was found that the efficiencies of the corresponding thermodynamic cycles were substantially the same as for the pure fluids used today. By changing the composition of the mixture, it was also possible to vary, within reasonable limits, the values of the condensation pressure, adapting the thermodynamic cycle to the different situations that can be encountered in current practice.